Analysis of The Effect of Institutional Ownership Profitability, Sales Growth And Leverage On Tax Avoidance On Construction Subsector Companies Listed On The Indonesia Stock Exchange - indrawan, muhammad isa indrawan; Rindi Andika; Abdul Razak Nasution; Henry Aspan; Solly Aryza (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This study aims to analyze the Effect of Institutional Ownership, Profitability, Sales Growth, and Leverage Against Tax Avoidance In Construction Subsector Companies listed on the Indonesia Stock Exchange in 2017 –2019, this research consists of 16 Construction Subsector companies listed on the Stock Exchange Indonesian Effect. by using the type of associative research analysis with data design the panel is a combination of time series data and cross-sectional data. The type of data used is panel data (pooled data), Regression analysis panel data with Fixed Effect Model (FEM) estimation method and reviews 10 SV programs. Hypothesis testing carried out is the Coefficient of Determination Test (R Square), F Test, and t-test. The results of the study show that the institutional ownership variable affects negative and positive effects on tax avoidance, Profitability Variable positive effect, and positive effect on tax avoidance. Variable Sales growth has a positive and positive effect on tax evasion. Leverage has a negative and positive effect on tax evasion.